KINERJA DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL DALAM TERTIB ADMINITRASI AKTA KEMATIAN DI KABUPATEN KAUR PROVINSI BENGKULU - Wawan Saputra B (AKSELERASI: Jurnal Ilmiah Nasional, 2021)
This study aims to analyze the performance of the Department of Population and Civil Registry of Kaur Regency, Bengkulu Province in carrying out orderly administration of death certificates. This study uses an exploratory approach with qualitative methods. Informants are selected based on internal and external information who really understand the problems that occur in the field. Qualitative data analysis was written descriptively. The results of this study indicate that the performance of the Department of Population and Civil Registration in the orderly administration of death certificates in Kaur Regency, Bengkulu Province in terms of productivity, service quality, responsiveness and responsibility is still not running optimally. The actions suggested by the author to improve the performance of the Population and Civil Registration Office in the orderly administration of death certificates are adjusting population and civil registration regulations, preparing programs that focus more on death certificates, making field monitoring teams as supervisors, making services through websites or applications on the one hand which facilitates and also improves the quality of information services.